Transmission and stable inheritance of carbapenemase gene (blaKPC-2 or blaNDM-1)-encoding and mcr-1-encoding plasmids in clinical Enterobacteriaceae strains - Xiaobo Liu (Journal of Global Antimicrobial Resistance, 2021)
Objectives: The aim of this study was to investigate the potential for transmission and heritability of carbapenemase gene (blaKPC-2 or blaNDM-1)-encoding or mcr-1-encoding plasmids in clinical Enterobacteriaceae strains. Methods: Potential for transmission of carbapenemase gene (blaKPC-2 or blaNDM-1)-encoding or mcr-1-encoding plasmids in clinical Enterobacteriaceae strains was tested in three conjugation models, namely filter-mating conjugation in laboratory conditions, a meat product model and the gastrointestinal (GI) tract of rats. Plasmid stability in Enterobacteriaceae strains was also determined. Results: We demonstrated that plasmids carrying a carbapenemase gene (blaKPC-2 or blaNDM-1) could be efficiently conjugated to strains carrying the mcr-1 gene and vice versa, and that these plasmids could stably co-exist in clinical Enterobacteriaceae strains. These findings suggest that Enterobacteriaceae can readily acquire phenotypic resistance to both carbapenems and colistin in natural environments such as food products and the GI tract of human and animals. Conclusion: Gene transfer events are common among members of the Enterobacteriaceae and serve as a key mechanism facilitating adaptation to new environments. Development of innovative strategies and surveillance measures to curtail the dissemination of multidrug resistance plasmids is necessary. Transmission and stable inheritance of these two types of plasmids would lead to the emergence of multidrug-resistant pathogens that are resistant to all currently available last-line antibiotics for Gram-negative bacterial infections.